PEMAHAMAN TENAGA KESEHATAN TERHADAP BERLAKUNYA UU NO.17 TAHUN 2023 - Gunawan Widjaja (JOURNAL OF COMMUNITY DEDICATION, 2023)
The aim of this research is to describe the understanding of health care for the enforcement of the Law (Law) No. 17 Year 2023 in Indonesia. This law is a major health regulation that has a major impact on health care practices, health care systems, and health care in the country. This research uses qualitative research with literary studies. The results of this study reveal that the healthcare authorities' understanding of Act No. 17 of 2023 varies, with some very well aware of the regulation, while others may still need further clarification. There were also varied reactions to the changes produced by this law, including a sense of challenge in adapting to the new regulations.